Malignant phyllodes tumor of the breast with lymph node metastasis: a case report - Vicentini, Guilherme; Linhares, José Clemente; Borsari, Gabriela; Linhares, Heloisa Zandoná (Mastology, 2025)
In the present case report we aim to describe a rare case of malignant phyllodes tumor in a young patient who presented with a fast-growing mass in the right breast, with an enlargement in the axillary lymph node ipsilateral to the lesion. Perioperative histopathological analysis confirmed malignancy in two out of five excised lymph nodes. Modified radical mastectomy was performed in the right breast, with axillary dissection levels I and II. One month after the first consultation, surgical margins were increased. The patient underwent adjuvant chemotherapy as a complement to surgical treatment. She had tumor recurrence 56 days after surgical treatment. The patient passed away six months after diagnosis.